Assessing microstructure and mechanical behavior changes in a Sn-Sb solder alloy induced by cooling rate - Schon, Aline Ferreira (2019)
In the present investigation a directional solidification experiment was performed in order to examine distinct microstructures related to different slices of the solidified Sn-2 wt.%Sb alloy casting. Such alloy is an alternative of interest with the target of replacing lead-containing solder alloys (containing 85 to 97 wt% of Pb) given that lead (Pb) is considered an important environmental complaint and has devastating effects on the human body. The imposed conditions in the present experiment may lead to solutal and thermal stability of the melt throughout solid growth towards the liquid. It was found that Sn-rich cells may prevail for cooling rates higher than 1.0 K/s whereas only Sn-rich dendrites appear for specimens solidified at rates lower than 0.3 K/s. The growth of dendrites is delayed when compared to previous results in the literature. In the presence of convective flow originated either thermally or solutally, β-Sn dendrites were reported to grow for samples solidified at rates as high as 1.5 K/s (i.e., 5 times higher). It appears that convection currents induce instabilities to happen at the solidification front and the growth of dendrites is benefited over such conditions. Tensile tests were also performed for Sn-Sb samples having distinct cellular and dendritic dimensions. It was found that unstable plastic flow happened during all tensile tests. The formation of bands along a specimen gauge was recognized as being a manifestation of the Portevin – Le Chatelier (PLC) effect. A homogeneous deformation stage preceded the start of serrations of stresses in the samples of the investigated alloy. The amplitudes of the serrations were found to be lower in the samples having cells as compared to those associated with dendritic microstructures